2004
DOI: 10.1162/003465304323031120
|View full text |Cite
|
Sign up to set email alerts
|

Local Revenue Hills: Evidence from Four U.S. Cities

Abstract: We provide estimates of the effects and long-run elasticities of the tax base with respect to tax rates for four large U.S. cities: Houston (property taxation), Minneapolis (property taxation), New York City (property, general sales, and income taxation), and Philadelphia (property, gross receipts, and wage taxation). Results suggest that three of our cities are near the peaks of their revenue hills; Minneapolis is the exception. A significant negative effect of a balanced-budget increase in city property tax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…The strong tendency of richer people to live outside of city borders suggests that they are voting with their feet within certain areas. Haughwout et al (2004) argue that these migration tendencies are quite strong and can mean that areas can actually lose revenue by raising taxes. Feldstein and Wrobal (1998) argue that the migration elasticities are so strong that states cannot effectively redistribute income at all.…”
Section: Government Policies and Local Inequalitymentioning
confidence: 99%
“…The strong tendency of richer people to live outside of city borders suggests that they are voting with their feet within certain areas. Haughwout et al (2004) argue that these migration tendencies are quite strong and can mean that areas can actually lose revenue by raising taxes. Feldstein and Wrobal (1998) argue that the migration elasticities are so strong that states cannot effectively redistribute income at all.…”
Section: Government Policies and Local Inequalitymentioning
confidence: 99%
“…On the other hand, local income tax surprisingly bears no relationship with local sales or meals tax. This is presumably because high- 15 The result from Haughwout et al (2004) might not apply to Massachusetts, because the effect could vary from state to state. In addition, the current paper does not adjust for potential employment relocations across the state border and associated wage losses, because existing literature is silent on the border effect for the payroll tax.…”
Section: Resultsmentioning
confidence: 99%
“…the per capita wage does not change with the imposition of a local payroll tax. Haughwout et al (2004) is the only paper found that estimates the elasticity of the per capita wage with respect to changes in the wage tax rate in the United States.…”
Section: Datamentioning
confidence: 99%
“…Successful and wealthy entrepreneurs with high incomes may be repelled by high income taxes, thus reducing the local supply of entrepreneurs (e.g., Haughwout et al 2004). Even entrepreneurs in low-skilled industries who choose sole proprietorship as the legal form may be more inclined to choose cities with low income taxes as their place of residence.…”
Section: Direct Effectmentioning
confidence: 99%